Walk the wire [large type] - Baldacci, David (Baldacci, David. Amos Decker series, 2020)
Amos Decker--the FBI consultant with a perfect memory--and Alex Jamison return to solve a gruesome murder of a young woman named Irene Cramer in a booming North Dakota oil fracking town. The promise of a second gold rush has attracted an onslaught of newcomers all hoping for a windfall--bringing with them problems--including drugs, property crimes, prostitution and now a gruesome murder.